ANALISIS KEPUASAN NASABAH ATAS KUALITAS LAYANAN INTERNET BANKING PADA PT BANK RAKYAT INDONESIA (Persero) Tbk. UNIT BANYUMANIK SEMARANG - Wahyu Febriyanti; Sri Widiyati (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2019)
The purpose of this research is to identify how to increase customer satisfaction of Internet Banking Service Quality at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Banyumanik Semarang with five dimensions of service quality which were tangible, reliability, responsiveness, assurance, and emphaty.Data in this research were obtained from questionnaires which spread to 100 (one hundred) respondents. The data analysis methods are validity test, reliability test, satisfaction index analysis, and satisfaction gap test.The results from reliability and validity tests showed that items of service quality dimension such as tangible, reliability, responsiveness, assurance, and empathy were valid and reliable. Based on the result of satisfaction index analysis, the weighting average score of Internet Banking quality service is 4,046. That score is between 3,43 – 4,23 which means satisfied. Based on the result of satisfaction gap test the increase of satisfaction established on the fifteen sub indicators show satisfaction, and three sub indicators show dissatisfaction, then it needs special attention and an improvement from PT Bank Rakyat Indonesia (Persero) Tbk. Unit Banyumanik Semarang for three sub-indicators are not satisfied.